“Tele-everything” world and hybrid office model – new global trends after the COVID-19 pandemic - E. V. Vasilieva (Управление)
As a result of forced social distancing and nationwide blockages, the habit of doing everything remotely has rapidly developed in society. The majority of work and household activities have been transferred to the Internet, and this has naturally led to the emergence of a new trend – “TV-everything” world.The rapid shift to a remote format and accelerated automation of processes have also changed attitudes to the previous management rules. The vast majority of companies decided during the pandemic to move some categories of staff to full-time remote work. One of the most debated topics today is the hybrid office model, where some employees work from home.The aim of the study is to show the consequences of the pandemic, which will determine the growth points in technology and management for the future, and to highlight the important challenges that the new norm of organisational management brings with it.The article presents the results of a survey of managers from various sectors carried out between March and April 2021. A review of the use of new technologies to improve the quality of the hybrid office was carried out. The importance of reinforcing the corporate culture in a remote working environment is highlighted and some guidelines for building communication in a remote working team environment are listed.These include: fostering corporate spirit, establishing a shared vision of the situation, mentoring, a culture of continuous feedback, informal communication, and newcomer adaptation.In a changing work environment, companies need to be extremely attentive to the well-being and productivity of teams and the mental health of employees. A number of measures have been proposed to monitor and improve the resource status of staff in organisations, including the use of computer systems that can conduct real-time assessments of employee performance and engagement based on artificial intelligence technologies.